Palladius and the Johannite Schism - Nuffelen, Peter van (The journal of ecclesiastical history, 2013)
The ‘Dialogue on the life of John Chrysostom’, published by Palladius of Helenopolis c. 408–9, is a key source for the history of the Church at the beginning of the fifth century. This paper argues that the history of the Johannite schism provides the background against which to understand the scope and nature of this work. It questions the received chronology of Palladius’ later life and shows that he is not so much a hard-core supporter of John who refused all contact with the official Church, as someone who could envisage the followers of John accepting an offer of amnesty in 408/409 and reintegrating into the Church. The dialogue is a strategic work that accepts that after the death of John (407) the Johannites can only bank on the support of Rome to improve their situation. As a consequence its trustworthiness cannot be accepted at face value.